Dark Lesion with Irregular and Polymorphous Vascularization in Two Patients: A Quiz - Carmen Couselo-Rodríguez; Laura Mesa-Álvarez; Hae Jin Suh-Oh; Carlos Álvarez; Ángeles Flórez (Medical Journals Sweden, 2020)
Abstract is missing (Quiz)